Learning in professional learning communities: shifts in mathematics teachers’ practices - Chauraya, Million; Brodie, Karin (Taylor & Francis (Routledge), 2019)
Professional learning communities as a form of teacher development have been in existence internationally for some time now and more recently in South Africa. Although strong claims have been made for their influence on teacher practices, very few research studies have investigated these claims. This paper presents a case study that connects teacher-learning activities in a professional learning community to shifts in teaching practices. Four high school mathematics teachers’ practices were analysed before, during and after their participation in a professional learning community. The results show that two teachers made modest shifts in three of the five key dimensions of their lessons and one of the two teachers sustained these shifts. The two other teachers did not make major shifts in their teaching. The shifts are linked to learning activities in the professional learning community, which involved the teachers in conversations about learners’ errors and learners’ learning needs, and designing lessons to address these needs. Findings from the study indicate how teacher-learning activities in a professional learning community can support shifts in teachers’ teaching and explain why changes differ among teachers.